The European Parliament ambassador school programme (EPAS) at Gimnazija Nova Gorica, Slovenia : Program "Škola ambasador Europskog parlamenta" u gimnaziji "Nova Gorica", Slovenija - Kobal, Martina (Array, 2020)
This paper will focus on the European Parliament Ambassador School Programme, whose aim is to create a permanently increasing network of schools across the European Union. Gimnazija Nova Gorica became part of the network in 2016, and since then the school has en-gaged with the Slovenian European Parliament Liaison Office, the European Parliament and its Members, and has carried out teaching activities that raise awareness of Europe, European democracy and citizenship at large. This paper will also demonstrate various activities and events organized by Junior Ambassador students at Gimnazija Nova Gorica and their mentors. Not only does the European Parliament Ambassador School Programme enable students to develop critical thinking, teamwork and problem-solving skills, but it also helps participants raise concerns about issues concerning the European Uni-on and develop their ideas for a better Europe in the context of multilingualism and multicultural EU policy.